Notch Signaling Contributes to Liver Inflammation by Regulation of Interleukin-22-Producing Cells in Hepatitis B Virus Infection - Wei, Xin; Wang, Jiu-Ping; Hao, Chun-Qiu; Yang, Xiao-Fei; Wang, Lin-Xu; Huang, Chang-Xing; Bai, Xue-Fan; Lian, Jian-Qi; Zhang, Ye (Frontiers in Cellular and Infection Microbiology, 2016)
The mechanism of hepatitis B virus (HBV) induced liver inflammation is not fully elucidated. Notch signaling augmented IL-22 secretion in CD4+ T cells, and Notch-IL-22 axis fine-tuned inflammatory response. We previously demonstrated a proinflammatory role of interleukin (IL)-22 in HBV infection. Thus, in this study, we analyzed the role of Notch in development of IL-22-producing cells in HBV infection by inhibition of Notch signaling using γ-secretase inhibitor DAPT in both hydrodynamic induced HBV-infected mouse model and in peripheral blood cells isolated from patients with HBV infection. mRNA expressions of Notch1 and Notch2 were significantly increased in livers and CD4+ T cells upon HBV infection. Inhibition of Notch signaling in vivo leaded to the reduction in NKp46+ innate lymphoid cells 22 (ILC22) and lymphoid tissue inducer 4 (LTi4) cells in the liver. This process was accompanied by downregulating the expressions of IL-22 and related proinflammatory cytokines and chemokines in the liver, as well as blocking the recruitment of antigen-nonspecific inflammatory cells into the liver and subsequent liver injury, but did not affect HBV antigens production and IL-22 secretion in the serum. Furthermore, IL-22 production in HBV non-specific cultured CD4+ T cells, but not HBV-specific CD4+ T cells, was reduced in response to in vitro inhibition of Notch signaling. In conclusion, Notch siganling appears to be an important mediator of the liver inflammation by modulating hepatic ILC22. The potential proinflammatory effect of Notch-mediated ILC22 may be significant for the development of new therapeutic approaches for treatment of hepatitis B.